Peningkatan Kemampuan Mahasiswa Dalam Materi Termodinamika Dengan Metode Tugas Mandiri dan Eksperimen Pada Program Studi Tadris IPA Fisika UIN Imam Bonjol Padang - Asrar, Allan (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The purpose of this study was to determine the improvement of student ability through independent tasks and experiment methods in the Science Tadris Study Program of Physics, UIN Imam Bonjol